WIPI proteins: Biological functions and related syndromes - Almannai, Mohammed; Marafi, Dana; El-Hattab, Ayman W. (Frontiers in Molecular Neuroscience, 2022)
WIPI (WD-repeat protein Interacting with PhosphoInositides) are important effectors in autophagy. These proteins bind phosphoinositides and recruit autophagy proteins. In mammals, there are four WIPI proteins: WIPI1, WIPI2, WIPI3 (WDR45B), and WIPI4 (WDR45). These proteins consist of a seven-bladed β-propeller structure. Recently, pathogenic variants in genes encoding these proteins have been recognized to cause human diseases with a predominant neurological phenotype. Defects in WIPI2 cause a disease characterized mainly by intellectual disability and variable other features while pathogenic variants in WDR45B and WDR45 have been recently reported to cause El-Hattab-Alkuraya syndrome and beta-propeller protein-associated neurodegeneration (BPAN), respectively. Whereas, there is no disease linked to WIPI1 yet, one study linked it neural tube defects (NTD). In this review, the role of WIPI proteins in autophagy is discussed first, then syndromes related to these proteins are summarized.